Determinants of SMEs' product innovation performance in Malaysia: an extended model - Maha Mohammed Yusr; Olayemi Abdullateef Aliyu; Amira Khattak; Maruf Gbadebo Salimon; Shoaib Muhammad (Cogent Business & Management, 2022)
This paper analyzes the organizational capabilities associated with new product development of SMEs in manufacturing companies with indicators such as administrative capabilities, functional capabilities (R&D, manufacturing, and marketing), and innovative performance (new product development) in Malaysia. This study develops an extended structural model linking administrative and functional capabilities to new product development. To empirically analyze these relationships, the researchers used a questionnaire-based survey to collect data from the managers of small manufacturing firms operating in Malaysia. A total of 159 usable questionnaires were received via an online survey of SME managers in Malaysia. The questionnaire was subjected to a PLS structural equation modeling analysis to establish quantitative relationships among constructs. This empirical study confirmed four out of the five hypotheses as statistically significant. SMEs will sustain their competitive advantage by integrating and effectively utilizing their capabilities in administration, manufacturing, and marketing resources. The positive but insignificant effect of the relationship between R&D and new product development can be attributed to the small sample size in this study. However, functional capabilities through the combined mean values of R&D, manufacturing, and marketing capabilities positively and significantly affect SMEs' new product development. The research framework offers a practical guide for SMEs to sustain their competitive advantage by integrating and effectively utilizing their administration, manufacturing, and marketing resource capabilities.
Keywords: 650; Innovation; competitive advantage; functional capabilities; manufacturing capabilities; marketing capabilities; R&D capabilities